Pokémon : Show Time! [anglicky] / Book 6 - West, Tracey, 1965- (Orchard Books, 2021)
A juggling Exeggutor, a singing Charmander and a dancing Farfetch'd can only mean one thing - it's time for the Pokémon Talent Show!Pokémon master-in-training Ash is determined to win. But when his enemies Team Rocket lure away his Pikachu, it's up to him to save all the Pokémon - and steal the show!